Structure of Hexakis(trimethylsilylmethyl)dimolybdenum: The First Compound Reported to have a Mo≡Mo Bond - HUQ, FAZLUL (Asian Journal of Chemistry, 2010)
The crystal and molecular structures of hexakis(trimethylsilylmethyl) dimolybdenum, Mo2(CH2SiMe3)6, were determined from three-dimensional X-ray diffraction data about 33 years ago using the facilities available at Imperial College, London, U.K. The crystals are monoclinic with unit-cell dimensions: a = 31.20 Å, b = 12.457 Å, c = 23.415 Å, β = 112.17°, space group Pc and Z = 8. The complex is dimeric and there are four crystallographlcally independent dimers, all having the same structure. In each dimer the two molybdenum atoms are joined by a short Mo≡Mo bond (2.168 Å) and each molybdenum atom has a distorted tetrahedral coordination, with Mo-C bonds of 2.124 Å. The configuration of the methylene groups in the dimer, which has approximately 32(D3) symmetry is staggered. The Mo-Mo triple bond is considered to be made up of dz2 orbitals forming the σ-bond and the overlap of two sets of dxz and dyz orbitals of both metal atoms forming the two π-bonds.